Effectiveness of Temulawak (Curcuma xanthoriza) and Kunyit (Curcumae domestica) Extracts to Enhance Productivity and as Immunostimulator of Avian Influenza in Broiler - Sufiriyanto, Sufiriyanto; Indradji, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
The objective of the experiment was to investigate the effectiveness of treating broiler with temulawak (Curcuma xanthoriza) and kunyit (Curcumae domestica) extracts to enhance productivity and as imunostimulator of avian influenza. Broilers were given either temulawak, kunyit or temulawak+kunyit extracts. The treatments, including a control, were arranged in a factorial design. Variables measured were production index and immune titter with haemaglutination inhibition (HI) test at 35 days of age. Results showed that control, temulawak-, kunyit- and temulawak+kunyit-treated chicken have production indexes of 302.80, 382.30, 327.71, and 358.30, respectively. HI test results were all negative. It can be concluded that neither temulawak, kunyit nor temulawak+kunyit extracts is effective imunostimulator of avian influenza in broiler. Nevertheless, temulawak-treated chicken showed highest production index.Â (Animal Production 9(2): 178-183 (2007)Â Key Words: Avian influenza, haemaglutination inhibition, temulawak, kunyit